The thanatological images in Barhev’s works: void, whistle and silence - Виниченко, Володимир Васильович (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2018)
The article deals with forms of artistic representation of the thanatological images in Barshev’s works. One of the most common forms of such representation is a void that allows to inscribe Barshev’s works in broad literary context (works of symbolists, Oberiu, Platonov’s prose). Overcoming death is shown to be connected with inventor’s image, that was ironically rethought in Flying Flammandrion, and motifs of blindness and insight. Also it refers to the motif of flying (for example in poems of Kharms) that turned out to be connected with the situation of disappearing, dissolution in void. The diverse Nothing opposes to the world of things, that in hypertrophied forms tends to degenerate into fire of things (according to A. Remisov), and water element that is endowed with a special power in Barshev’s works. Also the sound incarnation of the death images (the motifs of whistle, ring of bells) and connection between death and silence (quiteness, muteness) are considered in context of traditional beliefs.